Should the Same Side of the Market always move first in a Transaction? An Experimental Study - Eline C.M. van der Heijden; Jan H.M. Nelissen; Harrie A.A. Verbon (Tinbergen Institute, 2001)
This paper investigates whether transactions where the buyer (or the seller) always moves first, andthe seller (or the buyer) always moves second in the exchange gives higher payoffs than exchangesin which it is randomly determined who moves first. We examine the effect of two treatmentvariables: Partners versus Strangers and fixed versus changing positions. We find that both withfixed and with changing positions, second movers take advantage of their position by exploitingthe first mover by not delivering the demanded good. However, with fixed positions exploitationoccurs significantly less while reciprocal exchanges happen more often. In spite of this, it turns outthat with fixed positions payoffs are very unevenly distributed. Unequal payoff distributions occurboth under Partners and Strangers, but they appear to be more extreme among Strangers.
Keywords: C90; D63; 330; experiments; exchange; partners; role assignment; Spieltheorie; Theorie